2016
DOI: 10.1080/0142159x.2017.1248914
|View full text |Cite
|
Sign up to set email alerts
|

Attending rounds: What do the all-star teachers do?

Abstract: Specific categories of teaching activities-patient-specific teaching, teaching on learner-identified topics, and providing real-time feedback-are performed more frequently by the highest-rated attending physicians, which can guide faculty development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…& BHow am I doing?Ĉ onstant feedback There is no doubt that feedback is pivotal to the continuing growth of learners. The literature shows that constant, real-time feedback is one of the top determinants in who is considered an Ball-star^clinical teacher [5].…”
Section: And Bhelp Me Understand the Methods Behind The Madnessr Ime [12mentioning
confidence: 99%
See 1 more Smart Citation
“…& BHow am I doing?Ĉ onstant feedback There is no doubt that feedback is pivotal to the continuing growth of learners. The literature shows that constant, real-time feedback is one of the top determinants in who is considered an Ball-star^clinical teacher [5].…”
Section: And Bhelp Me Understand the Methods Behind The Madnessr Ime [12mentioning
confidence: 99%
“…There is no consensus on how best to conduct teaching rounds, but there is more agreement on what all teaching rounds should include, while being mindful not to overly extend rounding time. We have learned some things by exploring, for instance, what Ball-star^attendings do [5].…”
mentioning
confidence: 99%
“…7 However, a recent large-scale observational study has demonstrated that attending physicians who incorporated more bedside teaching activities per patient on rounds achieved higher resident learning satisfaction, yet actually spent less total time on rounds than their counterparts who performed equivalent amounts of teaching either in the hallway or conference room. 37 This is likely due in part to the redundancy of presenting a patient outside the room and then repeating elements of the history or exam at the bedside. Efficiency is ultimately operator dependent, but this is encouraging evidence that learners can benefit from bedside teaching while simultaneously delivering patient care.…”
Section: Practical Advantagesmentioning
confidence: 99%
“…Some have suggested a collaborative process to identify learning needs at the beginning of the teacher-learner interaction, such as the first day of a rotation or the start of a clinic session, 47,50 and this behavior clearly distinguishes more highly regarded clinical teachers. 37 When the teacher and learner will have prolonged contact, such as during an inpatient service rotation, collaborative determination of learning objectives should be an iterative process throughout.…”
Section: Preparationmentioning
confidence: 99%
“…But, if we ultimately believe that education should retain a key place on rounds then we need to understand how it could be optimised given the challenges of clinical medicine . Recent observational evidence linked higher learner satisfaction on rounds with three teaching activities: patient care‐related questions, real‐time feedback and learner‐driven topics . A review of ward round literature found agreement regarding the need to consciously structure rounds to maximise learning .…”
mentioning
confidence: 99%